PENGARUH PENDIDIKAN KEWIRAUSAHAAN TERHADAP POLA PIKIR KEWIRAUSAHAAN MAHASISWA S1 PENDIDIKAN EKONOMI UNIVERSITAS NEGERI SURABAYA - Divya Trizka Aprilina (FKIP Unswagati, 2025)
Through simple linear regression analysis, it can be concluded that Entrepreneurship Education has a significant influence on the Entrepreneurial Mindset. Entrepreneurship Education contributes to providing motivation and how to start a business, while Entrepreneurship Mindset contributes to how we view entrepreneurship. This research provides important implications for educational institutions to strengthen their role in supporting entrepreneurship development. Surabaya State University can design programs that facilitate supporting entrepreneurship. It is hoped that these findings can become a reference for further research and development of strategies to improve the entrepreneurial mindset among students. The population used as subjects in this study were undergraduate students of Economics Education class of 2023, Universitas Negeri Surabaya. In this study, a questionnaire was used as an instrument to obtain data. Data testing and analysis were carried out using SPPS software. Keywords: Entrepreneurship Education, Entrepreneurial Mindset, motivation.